Efeito da insolação na sanidade de abelhas Apis mellifera (africanizadas) no Semiárido Brasileiro - Souza, Franklin Amaro de (2016)
Africanized honey bees (Apis mellifera) from the region of the Semiarid Potiguar has two main diseases: varroatose, whose agent is the mite Varroa destructor and, the Nosemosis disease, recently introduced in the state, whose agent was previously identified in the area of our experimental apiaries as being the microsporide Nosema ceranae. The objectives of this study were to evaluate the effects of direct insolation and shading on the hives, in relation to the mite infestation rate in the adult bees and in the worker brood; on hygienic behavior and on the Nosemosis disease. The experiment was conducted in CETAPIS / UFERSA in the Mossoró-RN city. It were used 10 beehives installed under a metallic structure covered by dry leaves of coconut, it was built on the east-west direction, and with a capacity to absorbed about 90% of the direct insolation. Ten other beehives were installed under the direct effect of insolation, about 15 meters in relation to the former group. The results showed that during the dry season period the hives installed in the shade had an average infestation rate (%) in adult bees significantly lower (P <0.01) than in hives installed in the sun. Although the results show a smaller infestation trend on the bee brood of hives installed in the shade, no significant differences were observed (P = 0.253). Already hygienic behavior was very low, considering that the bees were Africanized bees and it were captured in the region during the swarming season. However, there was a significant negative correlation between the hygienic behavior and the mite infestation rate in adult bees. The nosemosis disease showed one prevalence of 100% in the experimental apiary, however, the average number of spores per bee can be considered very low, being significantly higher during the harvest period than in the off season period's, however, this results did not show significant differences between the hives receiving direct insolation and that ones under shade